Superlattice‐Stabilized WSe2 Cathode for Rechargeable Aluminum Batteries. Issue 12 (9th November 2022) - Cui, Fangyan; Han, Mingshan; Zhou, Wenyuan; Lai, Chen; Chen, Yanhui; Su, Jingwen; Wang, Jinshu; Li, Hongyi; Hu, Yuxiang
Abstract: Rechargeable aluminum batteries (RABs), with abundant aluminum reserves, low cost, and high safety, give them outstanding advantages in the postlithium batteries era. However, the high charge density (364 C mm −3 ) and large binding energy of three‐electron‐charge aluminum ions (Al 3+ ) de‐intercalation usually lead to irreversible structural deterioration and decayed battery performance. Herein, to mitigate these inherent defects from Al 3+, an unexplored family of superlattice‐type tungsten selenide‐sodium dodecylbenzene sulfonate (SDBS) (S‐WSe2 ) cathode in RABs with a stably crystal structure, expanded interlayer, and enhanced Al‐ion diffusion kinetic process is proposed. Benefiting from the unique advantage of superlattice‐type structure, the anionic surfactant SDBS in S‐WSe2 can effectively tune the interlayer spacing of WSe2 with released crystal strain from high‐charge‐density Al 3+ and achieve impressively long‐term cycle stability (110 mAh g −1 over 1500 cycles at 2.0 A g −1 ). Meanwhile, the optimized S‐WSe2 cathode with intrinsic negative attraction of SDBS significantly accelerates the Al 3+ diffusion process with one of the best rate performances (165 mAh g −1 at 2.0 A g −1 ) in RABs. The findings of this study pave a new direction toward durable and high‐performance electrode materials for RABs. Abstract : For the first time, a promising family of superlattice‐type tungsten selenide‐sodium dodecylbenzene sulfonate (SDBS) (S‐WSe2 ) cathode is proposed as cathode in rechargeable aluminum batteries (RABs) with stable crystal structure, and improved kinetic process. Benefiting from the unique advantage of the superlattice‐type materials, the anionic surfactant SDBS in S‐WSe2 stabilizes the structure and facilitates Al 3+ diffusion with long‐term stability and one of the best rate performances in RABs.